Total quality in higher education institutions and its role in embodying sustainable development - Mohamed Redouane DEHINA (Social Sciences Journal, 2023)
This study aimed to identify the contributions of total quality in the Algerian university and its role in achieving sustainable development, to answer the problem, we followed the descriptive approach. In order to find out and scrutinize this, the questionnaire of the quality of higher education and its impact on sustainable development was relied upon as a tool for collecting information. The study was conducted on a sample of (30) professors from university education. from Ammar Thaliji University in Laghouat. And we adopted the electronic method for withdrawing the sample items. After collecting the information and processing it statistically by means of SPSS 26, it was concluded that: The overall quality of higher education contributes to achieving the goals of the university. And good management and the competencies of its employees.